Enhancement of thermoelectric efficiency in Bi2Te3 via rare earth element doping. (15th March 2018) - Ivanov, Oleg; Yaprintsev, Maxim; Lyubushkin, Roman; Soklakova, Oxana
Abstract: The Bi2 Te3, Bi1.9 Lu0.1 Te3 and Bi1.9 Tm0.1 Te3 thermoelectrics of n -type conductivity were prepared by microwave-solvothermal method and spark plasma sintering. At the Lu and Tm doping, the Seebeck coefficient increases, while the specific electrical conductivity and total thermal conductivity decreases resulting in thermoelectric efficiency enhancement of Bi2 Te3 . It is believed that the thermoelectric efficiency can enhance mainly due to formation of narrow impurity Lu or Tm band with high and sharp density of states near the Fermi level. Both increase of the density-of-states effective mass of electrons and decrease of electronic contribution to the total thermal conductivity take place in this case. Graphical abstract: Image 1